Outcome of Functional Constipation in Children Age 1 to 12 Year in Tertiary Care Hospital - Muhammad Abbas, Mujtaba Gul, Tahira Nargis, Kashif Ali Khan, Furqan Ahmed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Both parents and children are bothered by constipation. Even then, it continues to go untreated, delaying medical intervention. It causes both physical and psychological morbidity. It has an impact on children's quality of life. The issue is exacerbated by delayed medical care. The young person could become less confident. Children may experience impaction of the faeces in 1%–3% of cases, which can result in faecal matter soiling. Aim: To investigate the outcomes of functional constipation in children between the ages of 1 and 12 in tertiary care facilities. Methodology: After receiving ethical approval from the committee, this cross-sectional study was conducted at Lady Reading Hospital in Peshawar from June 2021 to May 2022. The study included a total of 381 children’s. After obtaining parental assent, the ROME IV criteria was applied to the children who had functional constipation, and the children were treated according to the recommended recommendations and protocols. Result: 381 kids were enrolled in a study using the Rome IV criteria for constipation manifestation. The ratio was highest when passing 188 hard stools (49.34%) and lowest when passing 13 unpleasant stools (22.30%). Similar high ratio was observed in type-1 129(33.83%) of Bristol stool type. The ratio of males to females in the age range 3-6 year group was highest in the age group 6-12 year group, with 166 males and 63 females. The majority of restrooms (65.09%) were located outside door 248. Constipation-causing factors were shown to be highest in avoiding school lavatory use 181(47.50%) and lowest in opposing behavior 73(19.16%). History of food intake revealed a high ratio of 211(55.38%) from stores and a low ratio of 13(3.41%) from home-cooked meals. The hygienic care ratio was 178(46.71%) for not using water and soap and 19(4.98%) for using soap after using the loo.By exposing the concerns and their solutions for the health of their children, this will raise mothers' knowledge and be beneficial to society as a whole. Conclusion: All children need hygienic care and adequate education as a foundation. Dietary nutrition is crucial for growth. Children who are taken to the hospital may develop phobias and parents may experience problems. Children who are not properly treated for constipation are more likely to have serious psychological harm and bowel dysfunction. Keywords: Children, constipation, phobia, temper, education, food